2015
DOI: 10.1039/c5rp00084j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of the open-access ChemWiki resource as a replacement for traditional general chemistry textbooks

Abstract: Open educational resources (OERs) provide a potential alternative to costly textbooks and can allow content to be edited and adapted to a variety of classroom environments. At the University of California, Davis, the OER ''ChemWiki'' project, as part of the greater STEMWiki Hyperlibrary, was developed to supplant traditional post-secondary chemistry textbooks. The effectiveness of using this OER was assessed by comparing two general chemistry classes, one using ChemWiki and one using a traditional textbook, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 21 publications
2
53
0
1
Order By: Relevance
“…The authors found that the students using OER did just as well or better in most of the courses studied in terms of course grades and completion rates. Allen et al (2015) studied students in a chemistry course at the University of California, Davis who were assigned a traditional textbook (448 students) and students in another section of the same course taught by the same instructor (478 students) that used Chemwiki (https://chem.libretexts.org/)as a primary course resource (an openly licensed wiki site that can be used as a textbook). They found no significant differences in outcomes between these students, as measured through pre-and post-tests on content covered in the course, the same midterm and final exams, and the administration of the Colorado Learning Attitudes about Science chemistry survey (Barbera, Perkins, Adams, & Wieman, 2008), which asks about students' "beliefs on learning chemistry, content of chemistry, structure of chemistry, and connection of chemistry to the outside world" (p. 942).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the students using OER did just as well or better in most of the courses studied in terms of course grades and completion rates. Allen et al (2015) studied students in a chemistry course at the University of California, Davis who were assigned a traditional textbook (448 students) and students in another section of the same course taught by the same instructor (478 students) that used Chemwiki (https://chem.libretexts.org/)as a primary course resource (an openly licensed wiki site that can be used as a textbook). They found no significant differences in outcomes between these students, as measured through pre-and post-tests on content covered in the course, the same midterm and final exams, and the administration of the Colorado Learning Attitudes about Science chemistry survey (Barbera, Perkins, Adams, & Wieman, 2008), which asks about students' "beliefs on learning chemistry, content of chemistry, structure of chemistry, and connection of chemistry to the outside world" (p. 942).…”
Section: Introductionmentioning
confidence: 99%
“…They were assigned after the introductory lecture and due before the following class. The purpose was to provide learners with instant feedback on their understanding of the ChemWiki textbook readings (Allen et al, 2015), and prepare them for the in-class activelearning. Figure 1.…”
Section: Methods Courses Involvedmentioning
confidence: 99%
“…As such, pre-lecture videos were not provided to students. Instead, our flipped methods for general chemistry were designed around an instructor-personalized ChemWiki Hypertext (Allen et al, 2015), hence our use of the phrase text-centric flipping.…”
Section: Our Flipped Classroom Designmentioning
confidence: 99%
“…4 Allen, Guzman-Alvarez, Bowen, Chingos, Lack & Nygren, 2014;Fischer, Hilton, Jared-Robinson & Wiley, 2015;Hilton, Gaudet, Clark, Robinson & Wiley, 2013;Hilton & Laman, 2012. 5 Allen et al, 2015;Bowen et al, 2014;Hilton et al, 2013. 6 Hilton & Laman, 2012.…”
Section: Oers and Bpbs: Head To Headmentioning
confidence: 99%